The Fibrinolytic System in South African White and Bantu Men - Lackner, H; Johnson, A. J (Thrombosis and Haemostasis, 1967)
1. In a study of fibrinolytic activity conducted among South African Bantus and white males, the Bantus were found to have greater fibrinolytic activity, primarily because of higher levels of plasminogen activator.2. Levels of fibrinolytic inhibitors were similar in the 2 groups.3. The plasminogen level was significantly higher in the Bantus than in the South African whites, but it could not be correlated with fibrinolytic activity in individual subjects.4. Differences in serum protein patterns of Bantus and whites were confirmed.